When tough gets you going: Action orientation unfolds with difficult intentions and can be fostered by mental contrasting. (15th July 2020) - Friederichs, Katja M.; Kees, Marie-Christine; Baumann, Nicola
Abstract: Action orientation is a volitional mode that supports successful intention enactment under demands. We expected that priming difficulties evokes action-oriented individuals to self-regulate positive affect for effective intention enactment and causes state-oriented individuals to struggle. However, we predicted that mental contrasting increases intention enactment among state-oriented individuals. In two studies ( N 1  = 132, 46.21% male, M age  = 16.53; N 2  = 128, 61.72% male, M age  = 11.53), intention enactment was assessed non-reactively by Stroop interference. As a crucial test for self-regulatory ability, we used intention-forming primes ("setting high goals") which call for self-generating positive affect and presumably facilitate intention enactment only among action-oriented individuals. In Study 2, we aimed to improve state-oriented participants' intention enactment through mental contrasting. Consistent with expectations, action-oriented individuals showed a complete removal of Stroop interference after intention-forming primes (Studies 1 and 2). Furthermore, a short mental contrasting intervention promoted intention enactment among state-oriented participants (Study 2). Findings support the understanding that action-oriented individuals excel under demanding conditions whereas state-oriented individuals have to practice self-regulating positive affect to successfully enact under demands. Highlights: Novel and crucial non-reactive self-regulation test reveal individual differences. Action orientation: Volitional facilitation is evoked by difficulty. State orientation: Mental Contrasting supports intention enactment under demands. Affective change is a decisive mechanism for successful intention enactment. Outcomes help derive target-oriented interventions for improving self-regulation.